Contextually variable signals can be functionally referential. (February 2015) - Scarantino, Andrea; Clay, Zanna
Highlights: We offer a new definition of functional reference that highlights the role of contextual cues. The same signal can functionally refer to different things depending on contextual cues. Signals can be weakly correlated with what they functionally refer to. We distinguish two notions of meaning: meaning as correlation and meaning as reference. We compare and contrast our account with Wheeler and Fischer's (2012) meaning-based proposal.